ENVIRONMENTAL FACTORS’ INFLUENCE ON CORPORATE DECISIONMAKING AND ADAPTATION STRATEGIES - Santos, Miguel Reyes (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
In the face of intensifying market competition, companies are relentlessly pursuing enhanced operational efficiency. A pivotal determinant of improved operational efficiency lies in the company's managerial prowess. Employing incentive mechanisms, companies can attract and retain talent for extended tenures. These incentives empower employees to fully leverage their skills and capabilities, transforming passivity into proactivity, ultimately bolstering work quality and efficiency. Employee motivation serves as a catalyst, effectively harnessing employee enthusiasm and fostering a culture of innovation. As a result, employee performance experiences substantial growth.